PENGARUH TEKNIK KUNJUNGAN LAPANGAN TERHADAP KEMAMPUAN MENULIS PARAGRAF DESKRIPSI SISWA KELAS X SMA SWASTA PRAYATNA MEDAN TAHUN AJARAN 2012/2013 - DEWI SAFITRI RITONGA (Basastra, 2013)
This study aimed to describe the technique of site visits terhadap pengaruh writing abilities paragraf description of class X High School Private Lessons Prayatna Medaan Year 2012/2013. This study population is all private school students kelaas X Prayatna as many as 320 people. Samples were taken at random by 60 0rang, 30 0rang for experimental class and 30 for grade control. The instrument used was a test to write a paragraph description. The average value of the experimental class was 75.6, while for the control class is 68.6 Thus, it can be said that the average value of the ability to write a paragraph description of the experimental class higher than the control Kellas. Hypothesis testing is performed using test test "t". Test hypotheses derived from calculations thitung = 4.02, further consultation with the table at the significant level of 5% and 1% level of significance df = (N1 + N2) - 2 = 58. In the table t with df = 58 obtained TTable at 5% significance level = 2.00 and 1% significance level = 2.65. Testing criteria is rejected H0 if t0> tt. From the test results explained that t0 (4.02)> tt (2.65). This means that Ho is rejected. So we can conclude that learning techniques visits more influential than the expository technique to kemampuan students in writing a paragraph description Keywords: Effects, Engineering field trips, writing paragraf description